Influence of familial risk for depression on cortico-limbic connectivity during implicit emotional processing - Wackerhagen, Carolin; Schwarz, Kristina; Schweiger, Janina; Tost, Heike; Meyer-Lindenberg, Andreas (Neuropsychopharmacology, 2017)
Imbalances in cortico-limbic activity and functional connectivity (FC) supposedly underlie biased emotional processing and present putative intermediate phenotypes (IPs) for major depressive disorder (MDD). To prove the validity of these IPs, we assessed them in familial risk. In 70 healthy first-degree relatives of MDD patients and 70 controls, brain activity and seed-based amygdala FC were assessed during an implicit emotional processing task for fMRI containing angry and fearful faces. Using the generalized psychophysiological interaction approach, amygdala FC was assessed (a) across conditions to provide comparable data to previous studies and (b) compared between conditions to elucidate its implications for emotional processing. Associations of amygdala FC with self-reported negative affect were explored post hoc. Groups did not differ in brain activation. In relatives, amygdala FC across conditions was decreased with superior and medial frontal gyrus (SFG, MFG) and increased with subgenual and perigenual anterior cingulate cortex (sgACC, pgACC). NA was inversely correlated with amygdala FC with MFG, pgACC and their interaction in relatives. Relatives showed aberrant condition-dependent modulations of amygdala FC with visual cortex, thalamus and orbitofrontal cortex. Our results do not support imbalanced cortico-limbic activity as IP for MDD. Diminished amygdala-dorsomedial prefrontal FC in relatives might indicate insufficient regulatory capacity, which appears to be compensated by ventromedial prefrontal regions. Differential task-dependent modulations of amygdala FC are discussed as a stronger involvement of automatic instead of voluntary emotional processing pathways. Reliability and etiological implications of these results should be investigated in future studies including longitudinal designs and patient-risk-control comparisons.